Numerical modeling of phase-separation in binary media based on the cahn-hilliard equation - Gladkov, S.; Stiemer, M.; Grosse-Woehrmann, A.; Svendsen, B. (NTU "KhPI", 2009)
In the article numerical procedure for solution of the Cahn-Hilliard equation which is based on the forward Euler method in time and mixed (due to 4th order nature of differential operator) linear finite element formulation in space is described. Numerical examples consist of idealized model with double well potential (in 2 and 3 spatial dimensions) and more physically relevant model with logarithmic potential (in 2D only).

У статті описано процедуру наближеного рішення рівняння Кана-Хіллярда в частинних похідних 4-го порядку, котра базується на явному методі Ейлера в часі та змішаній постановці з білінійними скінченими елементами в просторі. Наведено чисельні рішення для ідеалізованої моделі з двуямним потенціалом (в 2-х та 3-х просторових вимірах) та більш фізично релевантної моделі з логарифмічним потенціалом (тільки в 2-х просторових вимірах).
Keywords: phase-field models; Euler method; logarithmic potential; polynomial free energy